2006
DOI: 10.1364/ol.31.002613
|View full text |Cite
|
Sign up to set email alerts
|

Large-area surface-plasmon polariton interference lithography

Abstract: Large-area surface-plasmon polariton (SPP) interference lithography is presented, which uses an attenuated total reflection-coupling mode to excite the interference of the SPPs. The interference of the SPPs causes a highly directional intensity range in a finite depth of the electric field, which is good for noncontact. Finite-difference time-domain simulations of the interference on a thin resist layer show that broad-beam illumination with a p-polarized light at a wavelength of 441 nm can produce features as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(42 citation statements)
references
References 14 publications
0
41
0
1
Order By: Relevance
“…In 2006, Guo et al proposed a large-area surface plasmon polariton interference lithography (LSPPIL) [50]. Figure 6.3 shows the physical arrangement.…”
Section: Prism-coupled Spps Nanolithographymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, Guo et al proposed a large-area surface plasmon polariton interference lithography (LSPPIL) [50]. Figure 6.3 shows the physical arrangement.…”
Section: Prism-coupled Spps Nanolithographymentioning
confidence: 99%
“…Being different from the former SPPs interference lithography [50] which requires a high refractive prism to be used, a low refractive prism could also be used to excite SPPs in the backside-exposure SPPIL device; however, due to the limited transmission distance of SPPs, it can pass through a resist layer only when it is thinner than 100 nm. The resonant condition of surface plasmon and resolution of interference patterns are varied with different thickness of the resist layer.…”
Section: Prism-coupled Spps Nanolithographymentioning
confidence: 99%
“…And it was demonstrated that the finer experimental results are easy to achieve at smaller incident angle [101]. Using this type of lithography system, 1D patterns using two-beam interference and 2D patterns using four-beam interference have been demonstrated [101][102][103][104][105][106][107][108][109][110][111]. The interferential beams are The plasmonic head flying 20 nm above the rotating substrate.…”
Section: Plasmonic Direct Writing Nanolithographymentioning
confidence: 99%
“…Unfortunately, the above plasmonics lithography methods are limited by the small interference areas or a mask grating with a very fine period. To overcome the two disadvantages, Du and coworkers [11] used the prism-metal-resist-substrate structure to realize the large-area maskless SPPs nanolithography. In the method, the two counterpropagating incident beams through the Kretschmann structure excite the counter-propagating SPPs in the interface of the metal and resist, and then the SPPs interference lines occur.…”
Section: Introductionmentioning
confidence: 99%